A cavitation-resistant copper alloy surface structure and preparation method thereof

Through laser impact forming technology, the hydrophilic structure on the surface of copper alloy is structured, which solves the cavitation problem of marine equipment, improves the cavitation resistance of copper alloy, and extends the service life of the equipment.

CN116497301BActive Publication Date: 2025-01-14HOHAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310326696.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-01-14
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The cavitation problems of marine exploration equipment such as propellers and thrusters at high-speed overcurrent components lead to fatigue and fall off of materials. The performance improvement of existing cavitation-resistant materials is limited, the coating cost is high and easy to corrode, and laser impact forming technology is in air resistance. The application of erosion is in the basic research stage.

Method used

The laser impact forming technology is used to form a hydrophilic structure on the surface of copper alloy. The energy converter composed of the constraint layer, absorption layer and protective layer forms a plasma shock wave, which realizes the plastic deformation of the material surface and the introduction of residual stress, and improves the surface wetness and resistance. Cavitation performance.

Benefits of technology

It significantly reduces the bubble generation rate, inhibits the cavitation process, improves the cavitation resistance of copper alloys, enhances surface density and microhardness, and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116497301B_ABST
    Figure CN116497301B_ABST
Patent Text Reader

Abstract

The present invention discloses a cavitation-resistant copper alloy surface structure and a preparation method thereof. The hydrophilic structure on the surface of the copper alloy is formed by laser impact forming technology. Based on the existing research on cavitation-resistant materials, the present invention uses a new processing structure with an added protective layer to texture the hydrophilic structure on the surface of the copper alloy by laser impact forming technology. The new processing structure with an added protective layer greatly improves the laser forming effect, and the surface of the prepared structure is smoother and flatter. The hydrophilic structure can improve the wettability of the copper alloy surface, reduce the gas nuclei near the solid-liquid contact surface, reduce the bubble generation rate, and thus inhibit the cavitation process; and introduce surface residual stress to increase the microhardness of the copper alloy, thereby further improving its cavitation resistance. The present invention can effectively inhibit the generation of cavitation, strengthen the material surface, and thus protect important components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cavitation-resistant surface micro-machining, and in particular to a cavitation-resistant copper alloy surface structure and a preparation method thereof. Background Art

[0002] Nowadays, in the context of economic globalization, the use and development of marine exploration equipment such as ships and underwater detectors have become extremely important. At the solid-liquid contact surface where the flow-through components such as propellers and thrusters move at high speed, the pressure or temperature in some areas changes greatly, causing the liquid in the area to partially vaporize and form bubbles, which is cavitation. As the bubbles gradually approach the solid-liquid contact surface, they lose the physical conditions to maintain the bubbles, and the bubbles continue to collapse, causing the liquid pressure around the material wall to increase suddenly. Due to long-term liquid scouring and bubble collapse erosion, the material surface is subjected to long-term repeated pressure shocks, and eventually the material fatigues and even causes the surface material to fall off. Cavitation on the material surface often occurs on the blade surfaces of water pumps, turbines and ship propellers, as well as on the local surfaces of high-head water discharge structures. Under the long-term action of cavitation, the equipment is prone to scars, cracks, and even defects. The surface of the pump casing and impeller becomes uneven, the friction coefficient gradually increases, the pump efficiency decreases, the power consumption increases, and it is easy to cause damage to the impeller, pump casing, etc., which will reduce the service life of the equipment by several or even dozens of years.

[0003] At present, there are two main means to improve the cavitation resistance of materials. One is to seek higher performance alloy materials and achieve ideal performance by doping trace elements in copper alloys; the other is to add high-performance coatings on the surface of materials, such as spraying organic coatings, supersonic flame spraying or laser cladding, to protect the internal metal substrate. At present, a large number of high-performance alloys have been used on marine materials, and the research and development of high-performance marine materials is in a bottleneck period, especially for cavitation-resistant materials, and it is difficult to significantly improve the performance. If a coating is used, although the cost is relatively low and it is also the most commonly used anti-cavitation method, the coating does not strengthen the base material, so it is necessary to replace the new coating regularly, which consumes a lot of manpower and material resources. In addition, after the coating is damaged, the metal elements in the coating are more likely to react electrochemically with the base material and corrode the base material. Laser shock forming technology is widely used in precision processing such as aerospace and is a complete technology. The preparation of hydrophilic structures by laser shock forming is still in the basic research and development stage. The preparation of hydrophilic structures by laser shock forming not only prevents damage to the material during mechanical processing, but also saves a lot of labor costs, which is very economical and convenient.

[0004] Nowadays, the research on the use of laser shock forming technology to prepare hydrophilic structures that are resistant to cavitation is still in the basic research stage at home and abroad. Laser shock forming technology is a forming technology that uses the force effect of high-amplitude shock waves induced by the interaction between high-energy pulsed lasers and materials to cause plastic deformation of sheet materials. Compared with traditional anti-cavitation processing technology, the use of laser shock forming technology to prepare cavitation-resistant hydrophilic surfaces has the following advantages: (1) High pressure, the deformation pressure reaches the GPa level, and any material can be processed; (2) High speed, a plastic deformation can be completed within tens of nanoseconds, and the preparation speed is faster; (3) After processing, a very high residual stress is formed on the surface, making the material more compact, further improving the cavitation resistance of the hydrophilic structure surface; (4) Flexible and changeable, by adjusting the laser incident angle, complex workpieces and different hydrophilic morphologies can be processed.

[0005] The present invention aims at the cavitation damage problem of flow-through components such as propellers and thrusters, and proposes to improve the cavitation resistance of copper alloys by texturing hydrophilic structures on the surface of copper alloys through laser shock forming technology. The laser impacts the energy converter (composed of a constraint layer and an absorption layer) on the surface of the workpiece, causing part of the atoms in the absorption layer to be vaporized and ionized to form a plasma shock wave, and then the pressure of the shock wave causes the plate to undergo plastic deformation, and the texturing process of the hydrophilic structure on the surface of the material is achieved through point-by-point impact and orderly distribution of impact points. The hydrophilic structure improves the wettability of the copper alloy surface, reduces the gas nuclei near the solid-liquid contact surface, reduces the rate of bubble generation, inhibits the cavitation process, and improves the cavitation resistance of the copper alloy. In addition, the laser shock forming technology not only brings about changes in the surface structure, but also introduces surface residual stress, which significantly improves the microhardness of the material and makes the surface material more dense, further improving the cavitation resistance of the copper alloy. Summary of the invention

[0006] In order to improve the cavitation resistance of copper alloys, the present invention provides a cavitation-resistant copper alloy surface structure and a preparation method thereof. The obtained copper alloy surface is not prone to produce hollow nuclei, reduces the cavitation formation rate, inhibits the cavitation process and introduces surface residual stress, thereby greatly improving its cavitation resistance.

[0007] The technical solution of the present invention is: a method for preparing a cavitation-resistant copper alloy surface structure, which mainly comprises:

[0008] The copper alloy components used in the present invention are 96.65-97.85% Cu, 1.6-2.35% Be, 0.2-0.35% Ni, 0.35-0.65% Co, and the remainder is iron and inevitable impurities. The experimental optical path of the present invention is that the laser emitted by the laser is focused on the workpiece through an optical system composed of a reflector, a condenser, etc. The laser impacts the energy converter (composed of a constraint layer, an absorption layer and a protective layer) on the surface of the workpiece, so that part of the atoms in the absorption layer are vaporized and ionized to form a plasma shock wave, and then the pressure of the shock wave causes plastic deformation of the plate, and the texture process of the hydrophilic structure on the surface of the material is realized through point-by-point impact and orderly distribution of impact points, such as Figure 1 shown.

[0009] (1) Material pretreatment: For copper alloy annealing, the stress relief annealing temperature is 150-200℃, and the holding time is 1-1.5 hours. It is used to eliminate the stress caused by cutting, rolling and other operations, stabilize the shape and size of the material in subsequent processing, and reduce defects; the annealed copper alloy is polished with 100-2000 mesh sandpaper, and then polished, cleaned, dried and other operations are performed to make the material surface as smooth as possible and reduce the roughness;

[0010] (2) Adjusting laser parameters; Fixing the copper alloy to be used in the laser shock action area, and adjusting the laser shock parameters to adjust the power density of the laser strengthening equipment: 4×10 13 W / m 2 --8×10 13 W / m 2 , pulse energy: 0.5-1J, pulse width: 5-10ns, processing frequency: 1-10Hz, wavelength: 1064nm, produces high repetition frequency, high energy, short pulse laser pulses, produces hemispherical pit-like structures on the surface of copper alloy, forming Figure 2 (a). And different surface morphologies can be processed by changing the laser incident angle, energy and other parameters. Adjusting the laser shock parameters is to adjust the power density of the laser strengthening equipment: 4×10 13 W / m 2 --8×10 13 W / m 2 , pulse energy: 1-1.5J, pulse width: 5-10ns, processing frequency: 1-10Hz, wavelength: 1064nm, incident angle: 45°, fish scale fan-shaped structure is generated on the surface of copper alloy, forming Figure 2 (b);

[0011] (3) Fixing the workpiece structure: fix a layer of rubber and aluminum foil on the surface of the copper alloy, with the rubber serving as a protective layer and the aluminum foil serving as an absorption layer. The structure specifically has the copper alloy substrate at the bottom, the protective layer in the middle, and the absorption layer aluminum foil at the top. Compared with the traditional laser shock forming technology, this structure adds a protective layer, so that the plasma and atomic chips generated by the laser will not be deposited on the surface of the copper alloy, making the surface structure of the material relatively smooth;

[0012] In addition, by writing a control program into the robot arm, the robot arm that fixes the material can be adjusted to move according to the established program trajectory, thereby realizing complex surface processing, as shown in the figure Figure 3 ;

[0013] (4) Laser loading: Start the laser impact equipment, and the laser emitted by the laser is focused on the copper alloy workpiece through an optical system composed of a reflector, a condenser, etc. The laser impacts the energy converter on the surface of the workpiece (composed of the outermost constraint layer, and the absorption layer and protective layer close to the workpiece, where the constraint layer is a water layer with a thickness of 1 to 2 mm. The purpose of the constraint layer is to control the propagation of the plasma shock wave into the material), so that part of the atoms in the absorption layer are vaporized and ionized to form a plasma shock wave, and then the pressure of the shock wave causes the plate to undergo plastic deformation. The texturing process of the hydrophilic structure on the surface of the material is achieved through point-by-point impact and orderly distribution of impact points. After the shock wave action is completed, the preparation of the surface structure of the cavitation-resistant copper alloy is completed, and the prepared structure is a hydrophilic structure, such as Figure 2 shown. Figure 2 (a) The diameter of the micropits in the structure shown is about 35-50 μm and the depth is about 20-30 μm; Figure 2 The sector radius of the structure shown in (b) is about 60-80μm, and the depth is about 10-15μm; the hydrophilic structure can improve the wettability of the copper alloy surface, reduce the gas nuclei near the solid-liquid contact surface, and reduce the bubble generation rate, thereby inhibiting the cavitation process and improving the cavitation resistance of the copper alloy.

[0014] Beneficial effects of the present invention:

[0015] 1. Laser shock forming is a new high-energy processing method in recent years. It is very suitable for the processing of marine operating equipment. The processed workpieces have the characteristics of good dimensional stability and high precision.

[0016] 2. The process is simple and feasible. After the workpiece is clamped at the predetermined position, the laser can be loaded on the copper alloy plate. The processing of a workpiece can be completed within tens of seconds or minutes, and the work efficiency is greatly improved.

[0017] 3. The surface of the workpiece is smoother. Compared with the traditional process, a protective layer is added to make the surface morphology of the processed material more

[0018] 4. The density, diameter and depth of the micro-pits are all controlled by laser-related parameters. Changing the parameters can be used to complete the processing of surface micro-pits with different requirements, and a variety of surface morphology textures can be achieved, which can be flexibly applied to various practical needs.

[0019] 5. The present invention is used for a method for preparing a cavitation-resistant copper alloy surface structure, which reduces the cavitation formation rate and improves the cavitation resistance of the copper alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the pulse laser acting on the metal surface in this example.

[0021] Among them: 1. Laser; 2. Laser beam; 3. Reflector; 4. Focusing lens; 5. Constraint layer (water); 6. Absorption layer (aluminum foil); 7. Protective layer (rubber); 8. Copper alloy; 9. Microstructure made on the surface;

[0022] Figure 2 Located on the surface of the copper alloy substrate, it is a schematic diagram of the finished product surface. (a) is pit-shaped, and (b) is fish scale-shaped.

[0023] Figure 3 Schematic diagram of the structure of a propeller specimen with a textured anti-cavitation structure surface layer.

[0024] 1. Sample base; 2. Surface texture area; 3. Robotic arm DETAILED DESCRIPTION

[0025] The present invention utilizes laser shock forming technology to obtain a hydrophilic structure on the surface of a copper alloy; based on existing research on anti-cavitation materials, the present invention uses a new processing structure with an added protective layer to texture a hydrophilic structure on the surface of a copper alloy through laser shock forming technology. The new processing structure with an added protective layer greatly improves the laser forming effect, and the surface of the prepared structure is smoother and flatter. The hydrophilic structure can improve the wettability of the copper alloy surface, reduce the gas nuclei near the solid-liquid contact surface, reduce the bubble generation rate, and thus inhibit the cavitation process; and introduces surface residual stress to increase the microhardness of the copper alloy, thereby further improving its anti-cavitation performance. The present invention can effectively inhibit the generation of cavitation, strengthen the material surface, and thus protect important components.

[0026] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0027] Example 1: Preparation of various hydrophilic structures on the surface of cavitation-resistant copper alloys, mainly including:

[0028] The copper alloy composition used is 96.65-97.85% of Cu, 1.6-2.35% of Be, 0.2-0.35% of Ni, 0.35-0.65% of Co, and the balance is iron and inevitable impurities.

[0029] The laser beam 2 emitted by the laser 1 is focused on the workpiece through an optical system composed of a reflector 3, a condenser 4, etc. The laser impacts the energy converter (composed of a confinement layer 5, an absorption layer 6 and a protective layer 7) on the surface of the workpiece, causing some atoms in the absorption layer to be vaporized and ionized to form a plasma shock wave. The pressure of the shock wave then causes the plate to undergo plastic deformation. The texturing process of the hydrophilic structure on the surface of the material is achieved through point-by-point impact and orderly distribution of impact points, such as Figure 1 shown.

[0030] (1) Material pretreatment: For copper alloy annealing, the stress relief annealing temperature is 150-200℃, and the holding time is 1-1.5 hours. It is used to eliminate the stress caused by cutting, rolling and other operations, stabilize the shape and size of the material in subsequent processing, and reduce defects; the annealed copper alloy is polished with 100-2000 mesh sandpaper, and then polished, cleaned, dried and other operations are performed to make the material surface as smooth as possible and reduce the roughness;

[0031] (2) Adjusting laser parameters; Fixing the copper alloy to be used in the laser shock action area, and adjusting the laser shock parameters to adjust the power density of the laser strengthening equipment: 4×10 13 W / m 2 --8×10 13 W / m 2 , pulse energy: 0.5-1J, pulse width: 5-10ns, processing frequency: 1-10Hz, wavelength: 1064nm, produces high repetition frequency, high energy, short pulse laser pulses, produces hemispherical pit-like structures on the surface of copper alloy, forming Figure 2 (a). And different surface morphologies can be processed by changing the laser incident angle, energy and other parameters. Adjusting the laser shock parameters is to adjust the power density of the laser strengthening equipment: 4×10 13 W / m 2 --8×10 13 W / m 2 , pulse energy: 1-1.5J, pulse width: 5-10ns, processing frequency: 1-10Hz, wavelength: 1064nm, incident angle: 45°, fish scale structure is produced on the surface of copper alloy, forming Figure 2 (b);

[0032] (3) Fix the workpiece structure; fix a layer of rubber and aluminum foil on the surface of the copper alloy, with the rubber serving as a protective layer and the aluminum foil serving as an absorption layer. Figure 1As shown, 1. laser; 2. laser beam; 3. reflector; 4. focusing lens; 5. constraining layer (water); 6. absorbing layer (aluminum foil); 7. protective layer (rubber); 8. copper alloy; 9. microstructure made on the surface; the structure is specifically copper alloy 8 substrate at the bottom, protective layer 7 in the middle, and absorbing layer 6 aluminum foil at the top. Compared with the traditional laser shock forming technology, this structure adds a protective layer, so that the plasma and atomic chips generated by laser induction will not be deposited on the copper alloy surface, which can make the surface structure of the material relatively smooth;

[0033] (4) Laser loading: Start the laser shock equipment. After the shock wave is completed, the preparation of the surface structure of the cavitation-resistant copper alloy is completed. The prepared structure is a hydrophilic structure, such as Figure 2 As shown (among which, the diameter of the hemispherical pit-like structure in a is about 50 microns, the depth is about 30 microns, and the center distance is 70 microns; each fish-scale-like microstructure monomer in b is a sector with a central angle of 45°, a radius of about 80 microns, a depth of about 15 microns, and a column center distance of 200 microns and a row center distance of 50 microns between microstructure monomers.). The hydrophilic structure can improve the wettability of the copper alloy surface, reduce the gas nuclei near the solid-liquid contact surface, reduce the bubble generation rate, thereby inhibiting the cavitation process and improving the anti-cavitation performance of the copper alloy.

[0034] Example 2: Propeller specimen with textured anti-cavitation structure surface layer, such as Figure 3 As shown;

[0035] Laser shock forming is performed on the plane of the sample. Figure 3 1. Sample base; 2. Surface texture area; 3. Robotic arm. During the implementation, the sample is immersed in water, and the water flow impacts and passes through the sample. After testing, it was found that:

[0036] (1) For workpieces that have not been processed, the cavitation process does not slow down, and the cavitation effect becomes more and more obvious as time goes by.

[0037] (2) After the workpiece is processed, the cavitation process slows down, the workpiece mass loss curve shows an inflection point, the cavitation incubation period increases, and the anti-cavitation effect is obvious.

[0038] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent methods or changes that do not deviate from the technical creation of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a cavitation-resistant copper alloy surface structure, characterized in that: The steps include: S1, pretreatment of copper alloy material; S2, adjust laser parameters; S3, fixed workpiece structure; S4, laser loading and impact forming to obtain a cavitation-resistant hydrophilic structure; In S1, the pretreatment is mainly to anneal the copper alloy, specifically: the stress relief annealing temperature is 150-200°C, and the holding time is 1-1.5 hours; the annealed copper alloy is polished with 100-2000 mesh sandpaper, and polished, cleaned, and dried to make the surface of the material flat and smooth; The copper alloy comprises: 96.65-97.85% Cu, 1.6-2.35% Be, 0.2-0.35% Ni, 0.35-0.65% Co, and the remainder is iron and other impurities; In S2, the laser parameters are set as follows: Adjust the power density of the laser strengthening device: 4×10 13 W / m 2 --8×10 13 W / m 2 , pulse energy: 0.5-1J, pulse width: 5-10ns, processing frequency: 1-10Hz, wavelength: 1064nm, produces high repetition rate, high energy, short pulse laser pulses; Under this condition, the hydrophilic structure of the copper alloy surface obtained in S4 is a hemispherical pit-like structure, with a diameter of 35 to 50 μm, a depth of 20 to 30 μm, and a center distance of 70 μm; In S2, the laser parameters or settings are as follows: Adjust the power density of the laser strengthening device: 4×10 13 W / m 2 --8×10 13 W / m 2 , pulse energy: 1-1.5J, pulse width: 5-10ns, processing frequency: 1-10Hz, wavelength: 1064nm, incident angle: 45°; Under this condition, the hydrophilic structure of the copper alloy surface obtained in S4 is a fish-scale fan-shaped structure, and the fan-shaped structure monomers are all fans with a central angle of 45°, a radius of 80 microns, a depth of 15 microns, and a column center spacing of 200 microns and a row center spacing of 50 microns between the microstructure monomers. The specific implementation of S3 includes: fixing a layer of rubber and aluminum foil on the surface of the copper alloy, with the rubber serving as a protective layer and the aluminum foil serving as an absorption layer; specifically, the copper alloy substrate is at the bottom, the protective layer is in the middle, and the absorption layer aluminum foil is placed on the top.

2. The method for preparing a cavitation-resistant copper alloy surface structure according to claim 1, characterized in that: The S3 also includes: by writing a control program into the robot arm, adjusting and fixing the robot arm of the material, complex curved surface processing can be achieved.

3. The method for preparing a cavitation-resistant copper alloy surface structure according to claim 1, characterized in that: The S4 comprises: starting the laser, the laser emitted by the laser is focused on the copper alloy workpiece through an optical system composed of a reflector and a condenser, the laser impacts an energy converter on the surface of the workpiece, the energy converter is composed of a constraint layer, an absorption layer and a protective layer, so that part of the atoms in the absorption layer are vaporized and ionized to form a plasma shock wave, and then the pressure of the shock wave causes the plate to undergo plastic deformation, and the texturing process of the hydrophilic structure on the material surface is achieved through point-by-point impact and orderly distribution of impact points.

4. A cavitation-resistant copper alloy surface structure prepared according to the method for preparing a cavitation-resistant copper alloy surface structure according to claim 1, characterized in that: The structure is a hemispherical pit-shaped structure, the diameter of the hemispherical pit-shaped structure monomer is 50 microns, the depth is 30 microns, and the center distance is 70 microns; the structure may be a fish-scale fan-shaped structure, each fish-scale microstructure monomer is a fan-shaped structure with a central angle of 45°, a radius of 80 microns, a depth of 15 microns, the column center distance between the microstructure monomers is 200 microns, and the row center distance is 50 microns.

Citation Information

Patent Citations

  • Method for improving cavitation resistance of material by using laser shock peening technology

    CN114410955A